Evaluation of University Students’ Chicken Meat Consumption Preferences and Knowledge of Chicken Production - Ali Kepezkaya; Nasir Abdallah; Kadriye Kursun; Mikail Baylan (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to evaluate university students’ chicken meat consumption preferences and their level of knowledge about chicken production. The survey was conducted with 61 structured online questionnaires using the Kobo-collect Tool Box. The questionnaires were administered online via student WhatsApp groups. Chicken breast meat was the most consumed with cubed meat being the most preferred. The expiration date was the main factor affecting chicken meat purchasing decisions, and the majority of the respondents did not have any preferred cooking method. Heavier meat (>1 kg) and fresh chicken meat were the most preferred with the highest chicken meat consumption of 1-3 times per week. Chicken meat consumption was highest at dinner and in the winter season with viral diseases being perceived as the most dangerous chicken diseases. The Coronavirus outbreak affected the chicken meat consumption of the majority of the respondents and most of them bought meat from reliable sale points. Most of the respondents could differentiate between slow and fast-growing broiler hybrids with Ross 308 being the most recognized commercial broiler hybrid by the respondents. It was concluded that chicken meat consumption was higher among the respondents however, agriculture students should be motivated to improve their knowledge about chicken production.